Total Quality Management, Partisipasi Anggaran, Sistem Penghargaan, Budaya Organisasi dan Kinerja Manajerial - Ari Pramesti, Putu Nadira; Asri Dwija Putri, IGAM (E-Jurnal Akuntansi, 2021)
The purpose of this study is to analyze the research of Total Quality Management (TQM), Budget Participation, Reward System and Organizational Culture of Managerial Performance. The population in this study is the General Manager and Department Managers in 5 hotels sheltered by Grandmas Hotels Group, with a sample of 60 people. Data collection method used is a survey method with a questionnaire technique. The regression model in this study uses multiple linear regression analysis. The results in this study indicate that TQM has a positive effect on managerial performance at Grandmas Hotels Group. Budget participation is positive for managerial performance at the Grandmas Hotels Group. The Rewards System has a positive effect on managerial performance at Grandmas Hotels Group. Grandmas Hotels Group provides positive support for managerial performance towards managerial performance. Keywords: Total Quality Management; Budget Participation; Reward System; Organizational Culture; Managerial Performance.